Developing home occupant archetypes: First results of mixed-methods study to understand occupant comfort behaviours and energy use in homes. (October 2019) - Ortiz, Marco A.; Bluyssen, Philomena M.
Abstract: To better understand home energy consumption, it is important to study the behaviours of occupants in their homes, especially in relation to their comfort needs. A mixed methods study comprising of a questionnaire, interviews, indoor environmental parameters monitoring, and energy consumption readings was performed to group home occupants based on their behavioural patterns. The TwoStep cluster analysis produced five clusters of home occupant with the data from 761 questionnaire respondents. The clustering model comprised of 28 variables including constructs of emotions, comfort affordances, and locus of control. Then, in-depth semi-structured interviews were conducted and IEQ monitoring and energy readings were taken with 15 of the questionnaire respondents. The results of the field study were used to substantiate the findings of the questionnaire. The combination of the statistical clusters with the data from the field study resulted in five archetypes: five distinct types of home occupants, differing in their behavioural motivations towards achieving comfort, and their use of energy when doing so. This study shows that a mixed methods approach is valuable for better understanding energy consumption and implementing archetype-customized lines of action to reduce energy use and maintain comfort. Graphical abstract: Image 1 Highlights: Mixed-methods approach consisting of a questionnaire, interviews, environmental monitoring, and energy readings. Strengthening previously-found statistical clusters with qualitative interviews data and quantitative building-related data. Qualitative and quantitative results allow describing home occupant archetypes in better detail. Five final archetypes define different types of occupants differing from their behavioural models.